WEB-BASED ELECTRONIC SALES INFORMATION SYSTEM AT THE ENGGAL SOURCE SHOP, CIREBON REGENCY - Rio Rinaldy (Green Publisher, 2022)
E-commerce web design on electronic sales aims to make it easier for people to obtain shopping information (online) which was previously known orally, so it does not save time, here I make it easier for people to do shopping online (online), so that it can be efficient and effective. This final project aims to build an online sales system. The design system in making e-commerce websites on electronic sales was developed using several software namely Macromedia CS6, XAMPP which is a combination of Apache Web Server, PHP and MySQL. By using Macromedia CS6, website work will be faster and easier. The tables used in making e-commerce in electronic sales are the category table, product table, admin table, city table, customer table, order table. All of these tables will later be used to accommodate the data needed in the construction of an e-commerce website on electronic sales